THE REFLECTION OF SHIA IDEOLOGY IN THE POETRY OF THE AQ TAPPEH FAMILY - Hadi, Parween; Ahmad, Dawlat (Humanities Journal of University of Zakho, 2025)
Throughout history, religious and spiritual beliefs have been important in shaping the culture of every nation which are clearly reflected in art and literature. The admiration for the Prophet Mohammed (PBUH) and his family, along with the respect for their actions, has always been evident. This includes the tragic event of the killing of Imam Hussein, Imam Ali’s son (PBUH), as well as the great importance placed on the life and actions of Imam Ali. These themes are central to Shia beliefs. We also see this reflected in the works of prominent poets and scholars, such as Sheikh Abdulrahman Aq Tappeh, Sheikh Muhammad Hasbi, and his sons, Sheikh Muhammad Karbalai and Sheikh Muhammad Askari. While these scholars were part of the Sunni tradition, their influence also affected Shia literature, and their works are important in understanding Shia themes in Kurdish classical literature. This has led to the recognition of the impact of Shia beliefs in Kurdish classical works and the works of poets from the Aq Tappeh family, who have been influential in Kurdish literary traditions.